Disaster Management Plans - Ikeda, Makoto (World Bank, Washington, DC, 2013)
Following its devastating experience with recent disasters, Japan has been strengthening or drawing up new disaster management plans at the national and local levels. The Great East Japan Earthquake (GEJE) revealed a number of weaknesses in planning for complex and extraordinary disasters. Central and local governments have been revising their plans to reflect what they learned from the GEJE. Japan's disaster management system addresses all phases of disaster prevention, mitigation and preparedness, and emergency response, as well as recovery and rehabilitation. It specifies the roles and responsibilities of national and local governments, and enlists the cooperation of relevant stakeholders in both the public and private sectors. Following the GEJE, assessments have been made of the capacity of existing disaster risk management (DRM) planning systems to prepare for and react to large-scale disasters. This report gives findings; lessons; and recommendations for developing countries. Revisions have been proposed, based on the lessons learned on March 11.